2013
DOI: 10.3390/md11124724
|View full text |Cite
|
Sign up to set email alerts
|

Toxic C17-Sphinganine Analogue Mycotoxin, Contaminating Tunisian Mussels, Causes Flaccid Paralysis in Rodents

Abstract: Severe toxicity was detected in mussels from Bizerte Lagoon (Northern Tunisia) using routine mouse bioassays for detecting diarrheic and paralytic toxins not associated to classical phytoplankton blooming. The atypical toxicity was characterized by rapid mouse death. The aim of the present work was to understand the basis of such toxicity. Bioassay-guided chromatographic separation and mass spectrometry were used to detect and characterize the fraction responsible for mussels’ toxicity. Only a C17-sphinganine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Even though Trichoderma species are commonly considered beneficial fungi, some Trichoderma strains, including T. harzianum , Trichoderma koningii , Trichoderma longibrachiatum , Trichoderma pseudokoningii and Trichoderma viride , maybe pathogenic to human [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Some marine Trichoderma were associated to contaminated mussels and some were even toxic to aquatic animals, such as Artemia larvae [ 25 , 88 ]. Therefore, evaluations of the adverse effects of our Trichoderma isolates on the environment and humans are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Even though Trichoderma species are commonly considered beneficial fungi, some Trichoderma strains, including T. harzianum , Trichoderma koningii , Trichoderma longibrachiatum , Trichoderma pseudokoningii and Trichoderma viride , maybe pathogenic to human [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Some marine Trichoderma were associated to contaminated mussels and some were even toxic to aquatic animals, such as Artemia larvae [ 25 , 88 ]. Therefore, evaluations of the adverse effects of our Trichoderma isolates on the environment and humans are needed.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of bioactive compound production is fundamental in understanding the complex ecological relationships established among and between sea-inhabiting organisms and microorganisms, and presents human nutritional implications due to the possibility that such fungal strains contaminate sea food, and their metabolites eventually act as mycotoxins [ 4 , 5 ]. However, the pharmaceutical industry can be regarded as the application field where products from marine fungi have the most substantial impact, since many of them have entered the clinical pipeline in view of being exploited as novel drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses made on contaminated mussel samples, i.e., positive Diarrheic Shellfish Poisoning (DSP) toxin test, revealed the absence of known marine biotoxins, as well as no relation between episodes of toxicity and harmful algal blooms [21], which suggests that mussel toxicity may be due to new toxin(s). Two fractions responsible for mussel toxicity were isolated using the bio-guided chromatographic separation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Two fractions responsible for mussel toxicity were isolated using the bio-guided chromatographic separation technique. LC-MS analyzes showed that the less retained fraction, identified and characterized by Marrouchi et al [21] and named C17-sphinganine analogue mycotoxin (C17-SAMT), has a molecular mass of 287,289 Da. The major effect of C17-SAMT on the mouse neuromuscular system in vivo was a dose-and time-dependent decrease of the compound muscle action potential amplitude and an increased excitability threshold.…”
Section: Introductionmentioning
confidence: 99%